2018
DOI: 10.2196/medinform.8895
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Physician Communication in the Era of Mobile Phones and Social Media Apps: Cross-Sectional Observational Study on Lebanese Physicians’ Perceptions and Attitudes

Abstract: BackgroundThe increased prevalence of virtual communication technology, particularly social media, has shifted the physician-patient relationship away from the well-established face-to-face interaction. The views and habits of physicians in Lebanon toward the use of online apps and social media as forms of patient communication have not been previously described.ObjectiveThe aim of this study is to describe the views of Lebanese physicians toward the use of social media and other online apps as means of patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…Apps that enhance patient engagement and safety, such as imito, have better chances of being adopted. This has also been described in other studies [ 89 , 102 , 129 , 130 ]. Similarly, there is a higher acceptance of apps that improve patient access to care [ 39 , 67 , 103 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Apps that enhance patient engagement and safety, such as imito, have better chances of being adopted. This has also been described in other studies [ 89 , 102 , 129 , 130 ]. Similarly, there is a higher acceptance of apps that improve patient access to care [ 39 , 67 , 103 ].…”
Section: Discussionsupporting
confidence: 87%
“…Given the highly regulated nature of health care, factors such as patient data privacy and security are vital for adoption. In the case of imitoCam, this factor was perceived as a facilitator, as the app offers a secure solution for clinical photo documentation, whereas other studies reported this as a barrier if data privacy and security could not be guaranteed [ 53 , 59 , 66 , 68 , 82 , 85 , 102 ]. Security requirements thus boost the adoptability of apps that can meet stringent requirements in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…For HCPs, patient education, career needs, and self-promotion were found to be the main factors that triggered them to participate in online interaction. More specifically, professionals saw patient education as a major driver of the use of online channels as tools [1,27,32-35,37], such as encouraging health behavioral changes and drug adherence, raising public awareness about specific health conditions, and eliminating misunderstandings about certain diseases. Moreover, career needs acted as a trigger for HCPs to provide online health care services [10,32,36-37], which in return provided them with opportunities for future career development.…”
Section: Resultsmentioning
confidence: 99%
“…Less than half of responding physicians in a study in Lebanon believed that web-based apps and social media could be useful for patient-physician communication. The other half (47.5%) was strictly against the use of virtual forms of communication as they feared breaching privacy and confidentiality[ 103 ]. In another study, physicians who frequently used the internet for professional use were more likely to take a positive position towards the use of the internet for communication with patients[ 97 ].…”
Section: Challengesmentioning
confidence: 99%
“…Online consultation is a possible solution for people living in rural areas or working full time. Practitioners feared this might be more time consuming and a threat to confidentiality[ 103 ]. However, studies have reported that the length of telemedicine consultations did not differ from that of the in-person consultations[ 104 ]; in some instances, online consultations were even time saving[ 101 ].…”
Section: Challengesmentioning
confidence: 99%